Surviving Hell Summer: Baton Rouge, Louisiana, racial polarization, and implications for community healing. Issue 3 (26th May 2020) - Grover, Leslie T.
ABSTRACT: Race matters in Baton Rouge, Louisiana. For centuries racial inequality has divided the city into two separate cities. In the summer of 2016, Baton Rouge experienced a series of events that heightened racial division. First was the killing of an unarmed black man, Alton Sterling, by two white police officers as he sold CDs outside of a local convenience store. Second was the shooting of three law enforcement officers and wounding of a fourth officer by a black ex-military shooter. By the time a massive flood took 13 lives and wiped out billions of dollars of property almost a month later, racial tensions were at an all-time high. Using Baton Rouge as a case study, this paper provides context for peeling back the layers of racial discord that have plagued the city for centuries.